Frequency dependence of organic magnetoresistance - Wagemans, Wiebe; Janssen, Paul; van der Heijden, E. H. M.; Kemerink, Martijn; Koopmans, Bert (Applied physics letters, 2010)
To identify the microscopic mechanisms of organic magnetoresistance (OMAR), the dependency on the frequency of the applied magnetic field is explored, which consists of a dc and ac component. The measured magnetoconductance decreases when the frequency is increased. The decrease is stronger for lower voltages, which is shown to be linked to the presence of a negative capacitance, as measured with admittance spectroscopy. The negative capacitance disappears when the frequency becomes comparable to the inverse transit time of the minority carriers. These results are in agreement with recent interpretations that magnetic field effects on minority carrier mobility dominate OMAR.